Forjando una nueva vida - Solórzano, Luis Diego; Solórzano, Luis Diego; Villalobos Vargas, Jorge; Villalobos Vargas, Jorge (UNED, 1984)
Expone el desarrollo de una nueva vida desde su concepción hasta el nacimiento.